ASSESSING THE RELATIONSHIP BETWEEN JOB SATISFACTION AND WORK-LIFE CONFLICT: PERSPECTIVES FROM THE UPPER WEST REGIONAL HOSPITAL IN GHANA - Nassè , Théophile Bindeouè; Guri , Ernestina Dakyire; Gyelaa , Joseph Wongnuo (International Journal of Business and Management Future, 2025)
Given the numerous problems related to job satisfaction and conflict in the workplace, a more thorough understanding of the various obstacles workers encounter in Ghana is crucial for offering long-term solutions. Additionally, work-life conflicts affect multiple sectors of activity, including the medical industry in Africa, particularly in Ghana. This present paper assesses the relationship between job satisfaction and work-life conflict at the Upper West Regional Hospital. The present research adopts a pragmatic worldview and employs an exploratory design and quantitative approach. Furthermore, this research investigates the relationship between job satisfaction and work-life conflict by collecting field data through paper questionnaires. For this research, a simple random sampling technique is used to select the respondents. The total number of health workers selected is 179. The research findings reveal a complex relationship characterized by a significant correlation between job satisfaction and work-life conflict, highlighting the multifaceted nature of employee experiences within the hospital environment. Nevertheless, the regression analysis further reveals an adverse effect of job satisfaction on work-life conflict. This finding suggests that management of the Upper West Regional Hospital should address employee concerns regarding pay, rewards, motivation, job security, improved wellbeing, and promotion opportunities, as these factors significantly influence overall job satisfaction and help mitigate work-life balance issues. To help managers, governmental authorities, and industry players understand the challenges faced by workers in the medical sector and provide long-term solutions, this research employs role theory to expand knowledge about job satisfaction and work-life conflict. JEL Classification Codes: M1, M5, M12, M52, M54.